2010
DOI: 10.1161/circulationaha.109.924167
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Left and Right Ventricular Endomyocardial Biopsy

Abstract: Background-Endomyocardial biopsy (EMB) represents the gold standard for diagnosing myocarditis and nonischemic cardiomyopathies. This study focuses on the risk of complications and the respective diagnostic performance of left ventricular (LV), right ventricular (RV), or biventricular EMB in patients with suspected myocarditis and/or cardiomyopathy of unknown origin. Methods and Results-In this 2-center study, 755 patients with clinically suspected myocarditis (nϭ481) and/or cardiomyopathy of nonischemic origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
285
10
26

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 393 publications
(336 citation statements)
references
References 35 publications
15
285
10
26
Order By: Relevance
“…In particular, performing an endomyocardial biopsy in the acute phase of myocarditis may be associated with higher risks, since the procedure is sometimes complicated by ventricular perforation of edematous myocardium, fatal arrhythmia and other fatal incidents. In contrast, the most recent study showed that the major complication rate for left ventricular endomyocardial biopsies is 0.64% and that for right ventricular endomyocardial biopsies is 0.82%, thus indicating a lower risk compared with previous reports (14). The recently published guidelines of the American Heart Association, the American College of Cardiology and the European Society of Cardiology state that new-onset heart failure of two weeks duration associated with a normal-sized or dilated left ventricle and hemodynamic compromise is a class I indication for a left ventricular endomyocardial biopsy (15).…”
Section: Discussioncontrasting
confidence: 59%
“…In particular, performing an endomyocardial biopsy in the acute phase of myocarditis may be associated with higher risks, since the procedure is sometimes complicated by ventricular perforation of edematous myocardium, fatal arrhythmia and other fatal incidents. In contrast, the most recent study showed that the major complication rate for left ventricular endomyocardial biopsies is 0.64% and that for right ventricular endomyocardial biopsies is 0.82%, thus indicating a lower risk compared with previous reports (14). The recently published guidelines of the American Heart Association, the American College of Cardiology and the European Society of Cardiology state that new-onset heart failure of two weeks duration associated with a normal-sized or dilated left ventricle and hemodynamic compromise is a class I indication for a left ventricular endomyocardial biopsy (15).…”
Section: Discussioncontrasting
confidence: 59%
“…16, 17 A key mechanism involved in adverse outcomes in HCM is believed to be myocardial fibrosis, which is a pathological hallmark of the condition, 18 and can be identified by biopsy. 19, 20 Recent studies of HCM patients suggest that the extent of fibrosis as measured by CMR correlates with histologically proven myocardial scarring 11 and is associated with worse prognosis, 10 including arrhythmic events. 6,9,21 However, in this study, fibrotic change (LGE %LV mass) by CMR-LGE did not reach statistical significance for the prediction of lethal arrhythmic events (HR=1.04, 95% CI: 1.00-1.10, P=0.06) ( Table 3).…”
Section: Clinical Significance Of Fibrosis In Hcmmentioning
confidence: 99%
“…In brief, to identify myocarditis, myocardial tissues were stained with hematoxylin and eosin, Masson's trichrome, and Giemsa following examination by light microscopy. Histological analyses were performed according to the Dallas criteria (22,23). Immunohistological analyses were used to investigate cardiac inflammation by treating the paraffin-embedded tissue sections with an avidin-biotin-immunoperoxidase method according to the manufacturer's protocol (Vectastain Elite ABC kit, Vectastain) (8).…”
Section: Methodsmentioning
confidence: 99%
“…In the light of cardiovascular diseases, human genetic studies exist only for patients with peripheral, central, or coronary atherosclerosis. These diseases occur with much higher incidence in comparison with DCM, which could explain the high number of included patients (23). Nevertheless, to the best of our knowledge, there is no larger well defined patient cohort of DCM that has investigated gene polymorphisms of innate immune proteins.…”
Section: Wild Typementioning
confidence: 99%